2020
DOI: 10.1002/ejic.202000415
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II), Zinc(II), Iron(III), and Copper(II) Complexes Bearing Positively Charged Quaternary Ammonium Functionalities: Synthesis, Characterization, Electrochemical Behavior, and SOD Activity

Abstract: We have synthesized and characterized Co(II) (1), Zn(II) (2), Fe(III) (3) and Cu(II) (4) complexes of 2,2'‐[2,6‐pyridinediylbis(ethylidyne‐1‐hydrazinyl‐2‐ylidene)]bis[N,N,N‐trimethyl‐2‐oxoethanaminium] dichloride (H2LCl2) by NMR, IR, and X‐Band EPR spectroscopy, respectively, as well as by single‐crystal X‐ray structural analysis. H2LCl2 belongs to the class of diacetylpyridine bis(hydrazone) ligands and bears two positively charged quaternary ammonium functionalities. The complexes 1–3 possess a pentagonal‐bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…While the redox pair C 1 /C 2 -C 2 ' is attributed to the behavior of gold (oxidation in C 1 and reduction in C 2 -C 2 '), the unexpected redox pair A 1 '/A 2 ' could be the trace amount of dissolved oxygen. 71 Similar to the above discussion in aqueous media, 32,61,[69][70][71] we hypothesize that the other observed redox A 1 /A 2 and B 1 /B 2 -B 2 ' peaks are due to the phthalocyanine ring reduction and oxidation, AuPc/[AuPc] − , [AuPc] − /[AuPc] 2− and [AuPc] 2− /[AuPc] 3− . The discrepancy in the behavior of redox processes between aqueous and non-aqueous electrolytes could be explained by competitive HER in aqueous media that reduce the potential window where we could observe all redox processes.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…While the redox pair C 1 /C 2 -C 2 ' is attributed to the behavior of gold (oxidation in C 1 and reduction in C 2 -C 2 '), the unexpected redox pair A 1 '/A 2 ' could be the trace amount of dissolved oxygen. 71 Similar to the above discussion in aqueous media, 32,61,[69][70][71] we hypothesize that the other observed redox A 1 /A 2 and B 1 /B 2 -B 2 ' peaks are due to the phthalocyanine ring reduction and oxidation, AuPc/[AuPc] − , [AuPc] − /[AuPc] 2− and [AuPc] 2− /[AuPc] 3− . The discrepancy in the behavior of redox processes between aqueous and non-aqueous electrolytes could be explained by competitive HER in aqueous media that reduce the potential window where we could observe all redox processes.…”
Section: Resultssupporting
confidence: 66%
“…7f and S16) demonstrates that the electrochemical process is in a mixed regime of adsorption and diffusion. [66][67][68] Leveraging on the existing electrochemistry literature of other metallophthalocyanines 32,61,[69][70][71] and gold porphyrin, 21,22 8a-8c where the "blank" refers to the absence of compound. In order to rationally assign the different redox processes, we performed control experiments using a bare gold electrode, which is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 Moreover, the metal complexes of diacetylpyridinebis(hydrazone) type ligands exhibit remarkable superoxide dismutase (SOD) activity. 20 Up to date, pyridine-based pentaazamacrocyclic ligands are one of the most prominent classes of non-peptidyl SOD mimetics. 21 SODs are a dedicated class of enzymes which are required to keep the concentration of the superoxide anion radical under a controlled low limit via the disproportionation of superoxide anion to molecular oxygen and hydrogen peroxide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Earlier studies revealed that the presence of positively charged groups (arginine moieties, quaternary ammonium groups) facilitates the interaction with the superoxide anion and significantly affects the SOD activity. 20,32 In addition to positively charged groups, the hydroxyl groups are also capable of altering the SOD activity. 34 In the iron, manganese, or nickel containing SOD enzymes, the role of the phenolic hydroxyl group of the tyrosine residue has clearly been confirmed.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation